Engineering peptide-polymer hybrids for targeted repair and protection of cervical lesions - Spencer, Paulette; Ye, Qiang; Misra, Anil; Chandler, Josephine R.; Cobb, Charles M.; Tamerler, Candan (Frontiers in Dental Medicine, 2022)
By 2060, nearly 100 million people in the U.S. will be over age 65 years. One-third of these older adults will have root caries, and nearly 80% will have dental erosion. These conditions can cause pain and loss of tooth structure that interfere with eating, speaking, sleeping, and quality of life. Current treatments for root caries and dental erosion have produced unreliable results. For example, the glass-ionomer-cement or composite-resin restorations used to treat these lesions have annual failure rates of 44 and 17%, respectively. These limitations and the pressing need to treat these conditions in the aging population are driving a focus on microinvasive strategies, such as sealants and varnishes. Sealants can inhibit caries on coronal surfaces, but they are ineffective for root caries. For healthy, functionally independent elders, chlorhexidine varnish applied every 3 months inhibits root caries, but this bitter-tasting varnish stains the teeth. Fluoride gel inhibits root caries, but requires prescriptions and daily use, which may not be feasible for some older patients. Silver diamine fluoride can both arrest and inhibit root caries but stains the treated tooth surface black. The limitations of current approaches and high prevalence of root caries and dental erosion in the aging population create an urgent need for microinvasive therapies that can: a) remineralize damaged dentin; b) inhibit bacterial activity; and c) provide durable protection for the root surface. Since cavitated and non-cavitated root lesions are difficult to distinguish, optimal approaches will treat both. This review will explore the multi-factorial elements that contribute to root surface lesions and discuss a multi-pronged strategy to both repair and protect root surfaces. The strategy integrates engineered peptides, novel polymer chemistry, multi-scale structure/property characterization and predictive modeling to develop a durable, microinvasive treatment for root surface lesions.